A TRANSITIVITY ANALYSIS ON THE HEADLINES NEWS ABOUT COVID-19 OUTBREAK IN JAKARTA POST AND CHANNEL NEWS ASIA - Sumarlin Putri, Novita; Mukhlish; Mulyani Darmastuti, Sri; Windra Puspita, Oktaviani (Wiralodra English Journal, 2021)
The Covid-19 outbreak currently striking Indonesia has caused a lot of information spread across all lines of mass media, from television, radio, printed and online media. The negative and unpleasant information about this outbreak has a negative impact on a person's psychology. Therefore, researchers analyzed the news in the Jakarta Post and Channel News Asia about Covid-19 outbreak because this news became a hot topic throughout 2020 to early 2021. This research has been done using a transitivity analysis of the Systemic Functional Linguistics theory by Halliday (2014) that argues in creating meaning in grammar can be represented in metafunctions: ideational (field), interpersonal (tenor), and textual (mode). The research findings show that there are 3 processes that often arise, namely verbal, material and attributive relational process. In addition, 1 mental process was also found in this study. Then, the participans sayer – verbiage, and circumstance of time also dominate in the finding.